The Influence of Digital Citizenship Education on the Legal and Moral Awareness of Generation Z - Layla Al-Hariri; Youssef Al-Mansour; Ahmed Hassam (Yayasan Adra Karima Hubbi, 2025)
Background. This study explores the influence of digital citizenship education on the legal and moral awareness of Generation Z. As digital technology becomes an integral part of daily life, it is essential to equip young people with the knowledge and skills necessary to navigate the online world responsibly. Digital citizenship education provides students with the tools to understand their rights, responsibilities, and ethical behavior in digital environments. Purpose. The objective of this research is to assess how digital citizenship education impacts the legal and moral awareness of Generation Z, particularly in terms of their understanding of issues like privacy, cyberbullying, intellectual property, and online conduct. Method. This study uses a mixed-method approach, combining a survey with 200 high school students and in-depth interviews with 20 educators. Results. The results indicate that students who participated in digital citizenship education demonstrated a significantly higher level of legal and moral awareness compared to those who had not received such education. Conclusion. The study concludes that incorporating digital citizenship education into the curriculum is effective in fostering a more responsible and ethical generation of digital citizens. These findings suggest that digital citizenship education should be a core component of educational programs to prepare students for the challenges and responsibilities of the digital age.